The politics of religion in the age of Mary, Queen of Scots : the Earl of Argyll and the struggle for Britain and Ireland - Dawson, Jane E. A. (Cambridge studies in early modern British history., 2002)
This book explains how the political crises of the mid-sixteenth century moulded the future political shape of the British Isles. Its central figure is the fifth earl of Argyll, the brother-in-law of Mary, Queen of Scots, and the major force throughout the Scottish Highlands and Lowlands.